Primary Sjögren's syndrome in men (1995)
OBJECTIVE--To describe the clinical expression of primary Sjögren's syndrome (SS) in men, focusing on extraglandular manifestations (EGM) and serological markers of disease. METHODS--In a cross sectional and comparative study, adult men with primary SS were identified from a cohort study on SS, and 26 age matched adult women with primary SS were selected as a control group. All patients met the European classification criteria for SS. They were compared for demographic, clinical and laboratory findings. RESULTS--Thirteen men with primary SS were identified. Mean age at onset was 39 (SEM 4) years and mean duration of disease was 7.8 (1) years. Sicca complex or parotitis was the presenting feature in eight patients (61.5%), and an EGM in five (38.5%). During the course of the disease, EGM were present in 12 patients (92%), polyarthralgias and lymphopenia being the most frequent (38.5% each). Rheumatoid factor was positive in 73% of patients, antinuclear antibodies in 85%, anti-(SS-A) in 62%, and anti-(SS-B) in 46%. No statistical differences in the frequency of EGM or in the presence of autoantibodies were observed between men and women. However, men patients were more likely to have EGM. CONCLUSION--Primary SS in men is an uncommon condition with clinical and serological characteristics similar to those observed in women. Sex hormones may be incriminated in the pathogenesis of SS. However, it remains poorly understood whether sex hormones play a major role in the severity of disease and have any importance with regard to treatment.